Analisis Hambatan Belajar Pada Pembuktian Induksi Matematika Dalam Kemampuan Pemahaman Matematis Mahasiswa - sholihah, wildatus (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
This article discusses the analysis of learning obstacles among students in mathematical induction proof. Mathematical induction proof is a crucial topic in developing students' logical and problem-solving skills, but many students face obstacles in comprehending it. Learning obstacles are analyzed based on the question indicators provided. Mathematical understanding in this research includes instrumental understanding and relational understanding. The study was conducted on 22 students from class 5A in the Mathematics Education Program at UIN Sunan Gunung Djati Bandung. The method used is descriptive qualitative based on the analysis of student responses. The research results consist of learning obstacles based on question indicators and indicators of mathematical understanding ability. Keyword: Learning Obstacles, Mathematical Induction, mathematical understanding ability.